Urban ecosystem services in the planning and design of urban green infrastructure for sustainable cities - Leone, Antonio (Plurimondi, 2025)
Green Infrastructure (GI) represents a network of natural and engineered ecological systems, located at the landscape scale and fully integrated with the built environment. GI provides a wide range of Urban Ecosystem Services (UES) and can enhance the resilience of urban systems to different categories of risk (e.g., hydrological risk and climate change). In particular, two main components of GI are presented and discussed: Non-Urbanized Areas (NUA) and Nature Based Solutions (NBS). NUAs include cultivated land, abandoned agricultural land, grasslands, woodlands and shrubs, often located at the edges of peri-urban cities, and they provide all main categories of ecosystem services. NBSs are techniques developed to control pollution, runoff and, in general, ensure sustainable urban water management, such as green roofs, permeable surfaces, constructed wetlands, retention basins, infiltration basins and filter drains. Ecosystem-service-aware GI planning and design, based on these components, can integrate human activities and the environment, considering both ecological and cultural/social aspects. A methodology for characterizing NUAs is presented as a planning support tool intended to improve current land-use patterns, with the aim of increasing the overall supply of ecosystem services in highly dispersed urban contexts. The capacity of GI to control urban stormwater is then discussed through a modelling approach applied to a compact district in the city of Bari.